Common Fixed Point Theorems of Greguš Type (ϕ, ψ)-Weak Contraction for R-Weakly Commuting Mappings in 2-Metric Spaces. (20th October 2015) - Parvateesam Murthy, Penumarthy; Devi Patel, Uma
Abstract : The main purpose of this paper is to establish a common fixed point theorem for set valued mappings in 2-metric spaces by generalizing a theorem of Abd EL-Monsef et al. (2009) and Murthy and Tas (2009) by using( ϕ, ψ ) -weak contraction in view of Greguš type condition for set valued mappings usingR -weakly commuting maps.